Comparison of Photodetector Performances in a Color Filtered Spectrophotometer - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2018)
In this study, the performances of phototransistor and phototube that can be used as a photodetector in a spectrophotometer device are compared. The spectrophotometer used is at a basic level and filters out the desired wavelength from broadband spectrum light through the color filter. With color filter, 16 different wavelength colors can be obtained. The filtered light falls onto the photodetector after passing through the pure water solution. It has been determined that the performance of the phototransistor is much higher in the experiments in which the phototransistor and phototube are used separately. The results of the experiments show that both the output amplitude and the measurement resolution are higher.